1953
DOI: 10.1139/p53-022
|View full text |Cite
|
Sign up to set email alerts
|

CROSS SECTION FOR THE REACTION Be9(γ, p)Li8

Abstract: The reaction Be9(γ, p)Li8has been investigated by detecting the 0.88 sec. Li8 β-activity, by the use of a cycling apparatus which allows intermittent operation of the betatron, counting taking place during the periods of no X-ray yield. The cross section for the reaction has a peak value of 2.72 mbarns at 22.2 Mev., a half-width of 4.7 Mev., and the integrated cross section to 26 Mev. is 0.013 Mev-barns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1959
1959
1978
1978

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In our experiments (Fig. 13) we did not see any resonance similar to the one observed in the reactions 39,40 Be 9 (7^)Be 8 or Be 9 (7^)Li 8 .…”
Section: Giant Resonancesupporting
confidence: 75%
“…In our experiments (Fig. 13) we did not see any resonance similar to the one observed in the reactions 39,40 Be 9 (7^)Be 8 or Be 9 (7^)Li 8 .…”
Section: Giant Resonancesupporting
confidence: 75%
“…These authors found a peak of height 3 mbarn at 22 MeV in the cross section derived from the yield of photoneutrons. If the 2·7 m barn found by Haslam et al (1953) for the peak cross section of the 22 MeV resonance of the 9Be(y, p) reaction is added to the 3 mbarn noted above, we may give 5·7 mbarn as the height of the 22 MeV giant resonance of 9Be. This giant resonance is considered to be due to electric dipole transitions.…”
Section: Analysis Of Resultsmentioning
confidence: 96%
“…This yield is composed of yields from both the (y,ao) and (y,n)'Be(16.6) reactions, i.e., where (JT = Oa0 + 016. 6 and 51 is the efficiency factor (18). Similar yields were found for the three other bremsstrahlung endpoint energies.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The photoproton rneas~lrements of Haslam et a/. (6) and Clikernan et a/. (7) were obtained by ~iieasuring the induced beta activity of 'Li and colisequently excluded any (y,np/pn) contribution.…”
Section: Introductionmentioning
confidence: 99%